Youth Suicide Deaths: Investigation of Clinical Predictors in a Statewide Sample. Issue 5 (22nd August 2017) - Keeshin, Brooks R.; Gray, Doug; Zhang, Chong; Presson, Angela P.; Coon, Hilary
Abstract : Death by suicide is a significant cause of mortality among youth. However, there is limited information on the demographic and clinical factors associated with youth suicide deaths. The objective of this study was to link large statewide databases to describe demographic, clinical, and cause of death characteristics among youth who died by suicide. We examined 1, 218 decedents under age 26 who died by suicie between 2000 and 2014. Eighteen died before age 12, 53 died between ages 12 and 14, 292 died between ages 15 and 18, and 855 died between ages 19 and 25. Most were male (83%), and firearm was most common cause of death; 28% previously attempted suicide, 31% had a mental health diagnosis, and 17% were prescribed psychotropic medication. Younger children died by hanging/smothering (89% of all 7‐ to 11‐year olds), and overdose/poisoning increased progressively with age. Adolescents had a higher proportion of females than young adults (23% vs. 14%, p  = .002). Combining data from the medical examiner and large hospital systems allows examination of youth suicide from a developmental perspective. Differences between age groups included gender, method, diagnosed mental illness, and diagnosis of attention deficit hyperactivity disorder. These data point to missed opportunities for effective interventions for specific developmental stages.